2019
DOI: 10.4314/ijbcs.v13i2.40
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte atresia in the Mangrove oyster, <i>Crassostrea gasar</i> (Dautzenberg 1891), (Bivalvia, Ostreidae) in tropical environment

Abstract: The mangrove oyster, Crassostrea gasar, is exploited in a natural state in the Casamance estuary in Senegal by rural women Diola. The decrease of its size on natural deposits and the remoteness of the harvesting areas, are at the origin of the Oyster culture project in Lower Casamance. It is in this context that the reproduction of the oyster, C. gasar in the Casamance estuary was studied between 1992 and 1994 to optimize its capture of its spats. Each month, a sample of about 30 adult oysters was collected at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
1
1
Order By: Relevance
“…However, the present findings contradict with Siddique et al (2020) and Diadhiou et al (2019) who reported spawning peak of this species during rainy season based on the histological observation of gonads. The potential reasons for this phenomenon could be attributed to the increased accessibility of food resources, favourable hydrological conditions, and enhanced opportunities for mating in the studied riverine water (Morriconi et al, 2002;Saeedi et al, 2009;Silva-Cavalcanti et al, 2018).…”
Section: Spent Stagecontrasting
confidence: 99%
“…However, the present findings contradict with Siddique et al (2020) and Diadhiou et al (2019) who reported spawning peak of this species during rainy season based on the histological observation of gonads. The potential reasons for this phenomenon could be attributed to the increased accessibility of food resources, favourable hydrological conditions, and enhanced opportunities for mating in the studied riverine water (Morriconi et al, 2002;Saeedi et al, 2009;Silva-Cavalcanti et al, 2018).…”
Section: Spent Stagecontrasting
confidence: 99%
“…Oocytes degenerate as a strategy to recycle the energy reserves used to mature oocytes and channel them to other tissues to cope with periods of stress and energy depletion (Beninger et al, 2017). In the tropical oyster C. gasar, gametes are not expelled and are recycled in the digestive system (Diadhiou et al, 2019). Here, we found that degenerated oocytes significantly increased at higher temperatures in both species (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…Mangroves (Rhizophora racemosa and Avicennia germinans) are characteristic of mangrove ecosystems and constitute the natural habitat of the mangrove oyster [9] . In Benin, the mangrove oyster is subject to artisanal exploitation at the coastal water levels especially in Lake Nokoué and the coastal lagoon [8,10] .Several scientific studies have been conducted on the reproduction, feeding and growth of the mangrove oyster [6,10,11,12] , but there is a lack of scientific data on rearing in controlled systems of the species. Oyster research is absent so that currently at the coastal lagoon, oyster farming remains traditional without any improvement.…”
Section: Introductionmentioning
confidence: 99%